Forecasting high-yield bond spreads using the loan market as leading indicator - Banu Simmons-Süer (ETH Zurich, KOF Swiss Economic Institute, 2013)
This paper attempts to find an aggregate leading indicator to predict the spreads observed for high-yield (HY) bond indices. Using a vector error correction (VEC) specification for quarterly data, we establish a long-term equilibrium relationship between the HY market spreads and its determinants, which stem from the interaction between the loan market via the banking sector and the HY market. The paper also attempts to explain the dynamic behavior of spreads by approximating the factors behind the credit and liquidity risk components. The out-of-sample forecasting properties of the resultant econometric model are shown to be superior to naive models.
Keywords: G12; G15; G17; 330; Unternehmensanleihe; Risikoprämie; Kapitaleinkommen; Prognoseverfahren; Rentenmarkt; Fehlerkorrekturmodell; Welt